Digital Games in Language Learning and Teaching - Edited by Hayo Reinders (New York Palgrave Macmillan, 2012)
Recent years have seen a growing interest in the pedagogical benefits of digital games, which have the potential to engage learners and to encourage interaction in the target language. The use of digital games in language education is based on the premise that successful learning is integrated into the sociocultural context of learners' lives and encourages collaboration and lifelong learning, bridging learning within and outside the language classroom. However, the potential of digital games has not been properly investigated from a second language learning and teaching perspective. This volume presents the first dedicated collection of papers to bring together the state-of-the-art in research into game-based learning. It includes theoretical, empirical, and practice-oriented contributions and as such will appeal to anyone with an interest in the most recent developments in language education. -- from Amazon.com.
Include Index
Keywords: Language and languages--Computer-assisted instruction -- Language and languages--Study and teaching--Technological innovations